NR gloves in contact with food: Factors affecting the protein transfer - Hasma H (Journal of Rubber Research, 2006)
Some NR latex gloves have been reported to transfer proteins to certain food on contact with gloves. The situation, however, could not be applied to all types of food and NR latex gloves. This study showed that no glove proteins were transferred to dry non-sticky food whereas the amount of proteins transferred to moist food is dependant on the extractable protein (EP) or antigenic protein (AP) content of the glove surface in contact with food. Glove contact surface of EP content <60 mg/dm3 or AP content of <1.5 Mg/dm3 could not transmit a measurable amount of proteins to nitrocullulose membrane which was used simulate food with high binding affinity for proteins. On the other hand, only gloves with a higher AP level of >10 mg/dm2 was found to transfer detectable amount of proteins to tomato and cheese. This inferred that NR gloves, especially powder-free gloves, with EP of <60 mg/dm2 and/or AP <10 mg/dm2 could be used in food handling.
Keywords: Antigenic protein; Extractable protein; Gloves; Nitrocellulose; NR latex; Protein transfer